Estimating Renovation Waste And Its Management In Seberang Perai Selatan A Case Study In Nibong Tebal - Zainul, Muhamad Faizal (Universiti Sains Malaysia, 2006)
Construction and demolition (C&D) waste is resulting from the construction, renovation or demolition of building structures. C&D waste will increase from time to time in proportion to the development of a town or country. Specifically, this study would be more on renovation activities around the area of Nibong Tebal housing schemes. A survey of 7 housing schemes throughout the area of Nibong Tebal was made from October 2005 until January 2006. In addition, in order to get the representative informations of waste handling and disposal, related information from Majlis Perbandaran Seberang Perai (MPSP) and Pulau Burung Sanitary Landfill were also considered. The total amount of waste generated regarding to renovation activity for all the housing schemes is about 49.64m3 .These amount of waste required 6 number of lorries (10 tonnes) to evacuate the waste which composed of 66 percent concrete and bricks, 15 percent of other wastes, 14 percent of woods and the other 5 percent is for steel and aluminum waste. Thus, the necessity of finding appropriate management and solution to C&D waste destination must be reliable and clear so that the waste is well managed.